Age and gender differences in static and dynamic balance of Chinese preschool children - Li, Ruiyuan; Liu, Meng; Zhu, Jiefeng; Li, Ruiqin; Zhao, Huan; Zhang, Liqing (Frontiers in Physiology, 2022)
Objectives: Balance is a crucial ability of early age, but there is conflicting evidence with regard to age and gender differences in preschool children's balance ability. Additionally, there are several tools available to measure balance, yet, wide variation in their use has restricted the capacity to synthesize the reference values. Therefore, the primary purpose of this study was to investigate the balance ability of preschool-aged children and determine how it is moderated by age and gender. The analysis pertained to determining whether different testing methods affect the results of static or dynamic balancing ability to provide a basis for normative balance ability data for healthy boys and girls between 3 and 6 years of age. Method: 619 preschool children aged 3–6 years participated in the study. The static balance (SB) was assessed with children standing on one leg (OST) and in a tandem stance (TS) for time spent. The balance beam test (BBT) and functional reach test (FRT) were used to evaluate dynamic balance (DB) by measuring the time spent and the distance reached, respectively. Result: The results revealed significant differences in OST with respect to gender (η2p = 0.037, P < 0.001), TS (η2p = 0.026, P < 0.001) and FRT (η2p = 0.016, P = 0.002); the girls performed better than boys on most balance tests except on BBT (η2p = 0.000, P = 0.596). Age had positive effects on the static and dynamic balance performance on the OST (η2p = 0.336, p < 0.0001), TS(η2p = 0.205, P < 0.001), BBT (η2p = 0.367, P < 0.001) and FRT (η2p = 0.392, P < 0.001). Older children performed better than their younger counterparts. No significant interactions between age groups and sex were found. Conclusions: This study revealed that static and dynamic balance stability in preschool-aged children was affected by gender and age. Girls displayed more excellent postural stability than boys, and balance performance improved with age. In addition, the study provides age- and gender-specific balance performance reference values for preschool children across multiple methods, which can be used to monitor static and dynamic balance development.